Effects of silkworm pupa protein on apoptosis and energy metabolism in human colon cancer DLD-1 cells - Xiaojiao Ji; Jing Wang; Aijin Ma; Duo Feng; Yue He; Wenjie Yan (Food Science and Human Wellness)
Objective: To investigate the effects of silkworm pupa (Bombyx mori) protein (SPP) on cell proliferation, apoptosis and energy metabolism in human colon cancer cells DLD-1. Methods: CCK-8 was used to detect cell proliferation rate after 72 h of cell culture for the control group (normal cultured DLD-1 cells) and SPP dose groups; Annexin-V/PI was applied to observe cell apoptosis; XFe24 Extracellular Flux Analyzer was used to detect cell mitochondrial respiratory function and glycolytic function. Results: Comparing with the control, SPP significantly inhibited the proliferation of DLD-1 cells with all the dosage tested (P < 0.01); flow cytometry showed that SPP significantly promoted apoptosis (P < 0.05). Additionally, SPP could significantly inhibited mitochondrial metabolism and glycolysis of DLD-1 cells and decreased cell energy metabolism in all groups treated with different doses. Conclusion: SPP can cause oxidative damage, promote apoptosis, and reduce mitochondrial respiratory and glycolysis rate in colon cancer DLD-1 cells, which reveals that SPP has the potential to serve as the anti-cancer drugs in the future, but further experimental evidence is needed.